Modeling the flood response for a sub-tropical urban basin in south Florida - Stella, Juan M.; Anagnostou, Emmanouil N. (Tecnología y ciencias del agua, 2018)
A key area of research in hydrologic modeling is the prediction of flood response in complex urban basins with hydraulic structures such as pump stations, canals, culverts, and spillways. The prediction of the basin’s response to heavy rainfall is needed in order to assess the impacts of potential watershed management decisions, especially during high flow periods. In this study, the HEC-HMS model was adopted to predict the accumulated discharges in a small urban basin located in West Palm Beach, Florida, USA. The model was calibrated based on seven flood events and validated using seven independent events spanning a 5-year period. The results show that the accumulated flow of water released from the basin was simulated with high accuracy, and that the model can be used for various management scenarios involving high flow conditions in the south Florida urban basin.